Characters of Vulnerability of Girls to Commercial Sexual Exploitation of Children (CSEC): Case Studies in Lombok and Jakarta - Bagus Yaugo Wicaksono (Jurnal Perempuan, 2020)
The victims of commercial sexual exploitation of children (CSEC) -especially girls- both in Jakarta - and Lombok area are having unique characteristic of vulnerability, therefore in order to optimize supporting the victims, an understanding of these characteristics of vulnerability in both areas are required. The purpose of this article is to describe and analyze the implementation of Down to Zero Project conducted by Plan International Indonesia (PII) in North Jakarta, East Jakarta, West Lombok, and Central Lombok. By conducting desk review of documents and results of previous studies during the implementation of this project, this study argues that; first, on the one side, the vulnerability of CSEC victims in Lombok areas tends to have a relation with poverty, furthermore the strict norms and value of custom could be challenging. On the other side, ineffective protection from family or caregiver makes a huge challenge for CSEC victims in the Jakarta area, in addition a heterogenous society and individualist characters create ineffective social protection for them. Secondly, these differences showed that the existing child protection system for girl victims of CSEC is not fully able to support them to reach the quality of life.